ANALISIS FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN PENERAPAN STANDAR ASUHAN KEBIDANAN OLEH BIDAN PRAKTIK SWASTA - Yuniwati, Yuniwati (JURNAL MEDIA KESEHATAN, 2015)
The results of research from the Author on November 2013 through observation usingcheck list and documentation care to the 20 persons midwife in Bengkulu City, there is 4 persons(20%) midwife who implementation of documentation care as standard. Whereas as much as 16midwives (80%) were not doing documentation care as standard. The aim of this research wasknowing the factors related to implementation of application of Midwifery Care Standards inMidwives Practice Independently in Bengkulu City 2014. This research used descriptive analyticwith Cross Sectional Approach. Population are all of the midwives who duty in Public HealthCare of Bengkulu City. Samples taken using purposive sampling method (50 respondents).Primary data collection and data analyzed univariate, bivariate and multivariate manner. Resultsof research showed that most of respondents (56%) had good education about implementation ofMidwifery Care Standards by Midwives Practice Independently, Most of respondents (66%) hadhigh motivation, most of respondents (72%) had good of supervition perception, most ofrespondents (66%) had good implementation of Midwifery Care Standards. There wascorrelation among education (π =0,026), motivation (π =0,008) supervition perception (π =0,003)with implementation of Midwifery Care. Standards Motivation factor was the most dominantfactor that affected implementation of Midwifery Care Standards by Midwives PracticeIndependently on 2014. Health Department of Bengkulu City should give instruction to all thePublic Health Care of Bengkulu City to perform documentation with guidelines of MidwiferyCare Standards.